Best interest of child in an information society abstract - Morales de Ferreyros, Sylvia Torres (2009)
The immersion in the so called "Information Society" indudes, nowadays, not only adults who are able to process the informarion they receive, to evaluare it, and before acting, distinguish berween good and bad, but also children who are more more consumers of a world called "Internet". For that reason, it is important to  analyze and question rhe fact thar alrhough informario n rechno logy provides us wirh many opporruniries of growing, It can also become a dreadful tool if the existence of regulations necessary to protect our children from immment information they receive is not guaranteed. The objective of legislations has always been the research of the child’s best interest, the society of information must then try to be compatible to avoid clashing against this universally recognized Doctrine. The present article will analyze this topic from a particular case that has become in our country a very productive business: the internet café as a means for transmission of information.